THE IMPLEMENTATION OF POSITIVISTIC PRINCIPLE IN QUALITATIVE RESEARCH - Pratama, Ade Setia; Mukhlis, Prof. Dr. Imam (UTSAHA: Journal of Entrepreneurship, 2023)
Nowadays, mainstream scientific research activities have been carried out using two methods or approaches, the first is quantitative (positivistic) by testing hypotheses as evidence and the second is qualitative (post-positivistic) by analyzing case studies, phenomena to measure the depth of formal aspects in assessing subjective events that occur in the field. This research provides a thorough understanding to identify the differences between positivistic and post-positivistic lines of thought and review the mutual combination of positivistic thinking with qualitative-based research activities which tend to be at odds. This research was conducted through library research method. Reference sources are obtained from books, journals and other relevant references. The results of this research indicate that positivistic thinking of thought does not tend to be an obstacle to conduct a qualitative research. This is proven by the emergence of several theories that can be used as analytical tools to provide additional references to support the validity of data collection in the field.